SISTEM PEMBELAJARAN MENGGUNAKAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM BIDANG PENDIDIKAN (E-education) - Imam Mualim (LPPM Universitas Muhammadiyah Kotabumi, 2020)
The current development of information and communication technology provides various communication facilities for exchanging information so that place, time and distance are no longer an obstacle in solving various affairs. The rapid development of information and communication technology cannot be separated from the development of computer engineering tools. Advances in computer science and information technology today also have a very positive impact on the field of education in learning. The most influential application in the field of computer technology and information technology in an education sector is the use of computer network devices and the internet. With the internet, all information services on educational targets are not limited to space, place, time and distance. Through internet network services, information can be provided as a learning resource, this learning medium that can be studied according to the needs and speed of learning of students and the learning process. This learning media is not limited to letters or images but all can be combined with various things such as graphics, animation, video, audio together so that this learning media is better known as a multimedia. The positive influence of the use of an internet for education in building education must be able to keep up with developments in science and technology (IPTEK). Applications include the world of industrial companies so that alumni are able to meet the demands of competency abilities. Based on these facts, one way to be able to keep up with the development of Technology Science (IPTEK) is always updating and all of this can be obtained through internet media. However, in its implementation, there are still many needs to support facilities and infrastructure, managers and users of information. In addition, great motivation rose from teachers to be able to control and optimize the use of ICT for teaching and learning in the classroom.